EDP managing a new electricity era: the birth of ocean winds/ harnessing wind energy to upscale development: how EDP´s joint venture with engie transformed the renewables´ market in Portugal - Matias, Leonor Teruszkin (2022)
Renewables are undeniably revolutionizing the energy sector. In particular, the attractiveness of offshore wind energy has been growing over time and presents itself as paramount towards achieving major sustainability milestones. The approach to grow and overcome challenges in the offshore wind sector relies on partnerships for value creation. This work project focuses on the EDPR pioneer position in offshore wind energy and how this industry will favorably impact climate change and build a more sustainable future. It also evaluates partnerships for this industry, including the joint venture between EDPR and Engie (Ocean Winds), and their importance towards strengthening energy transition.